The Hidayat al-habib fi al-targhib wa al-tarhib: a pioneer work of hadith in Malay Archipelago by al-Raniri - Latifah Abdul Majid, (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2017)
This article presents an investigation on a part played by al-Raniri in disseminating Hadith teaching in Malay Region. Special attention is given to his techniques of writing Hadith in order to facilitate a better understanding of the Hadith to Malay readers and also his connections with his teachers and the chains of his teachers with leading Islamic scholars in the Middle East. In the interest of validity and reliability, the study provides multiple sources of evidence including in-depth interviews with expert in the field of seventeenth century education and biographers of the great scholar. Also, from previous documentations and content analysis. The study is qualitative and the approach is hermeneutic. This article upon the earliest Hadith writing in the Malay world would assist in understanding, the importance of Hadith in Malay-Islamic history and its recognition by the devout and how it came to be regarded as part of Islamic Scripture.